Student Youth Employability and Employment Management in modern conditions - V. Moroz, Victoriya (2020)
The relevance of this article is to understand the problem of employment of graduates. Currently, in a market economy in Russia there are changes in the sphere of labor and employment. There is a tightening of conditions for young professionals to enter the labor market, which allows us to talk about unemployment, which in turn exacerbates the difficult situation of the Russian economy. Especially dangerous is the high unemployment rate among graduates of higher education institutions, because they are considered the most promising group in the working population. The aim of the study is to analyze the satisfaction of University graduates with the activities of employment departments. The leading method for the study of this problem is the method of the questionnaire, which indicates the units, which are ordered in a logical sequence, that it contribute to the effective identification of the degree of students’ satisfaction with implemented activities and employment. The article analyzes the concepts of employment and employability, their essence and the existing problems of students and graduates’ employment. The experience of research in the study of work within University organizations to promote the employment of students is analyzed. The novelty and originality of the study lies in the fact that the phenomena of employment and employability of students are analyzed. The problems of graduates associated with their employment are considered: lack of professional activity experience and work experience; lack of jobs of a certain specialty; complexity of employment associated with gender and age characteristics; lack of knowledge and skills to negotiate with employers on employment; poor awareness of young people about the features of various professions and labor market forecasts, and others. It is determined that in addition to studying at the University, more than half of the respondents do not work on a permanent basis. It is shown that the most common channels of information when searching for a job for students are the Internet and appeal to relatives and friends. It is revealed that most of the students believe that the University should provide assistance in employment and as the most popular way to promote employment on the part of the University by the students is noted the organization of meetings with employers. At the same time, more than half of the respondents did not attend employability promotion events held by the University. It is analyzed that the most common reason for non-attendance was the lack of informing of students. It is revealed that among the advantages of the events conducted, students noted a large number of employers, the organization of the event and getting answers to questions. It is determined that the main drawback of the events students consider the lack of information about the necessary vacancies and the lack of vacancies for students of humanitarian specialties. It is shown that the majority of respondents believe that the structure of employment should definitely be in every University. The data Obtained in the work can be used in labor psychology, age psychology, social psychology, pedagogy, sociology, as well as for further theoretical development of this issue.